2020
DOI: 10.1002/nafm.10409
|View full text |Cite
|
Sign up to set email alerts
|

In‐Stream Egg Incubators Produce Hatchery Chinook Salmon with Similarities to and Differences from Natural Juveniles

Abstract: Supplementing fish populations at the egg stage is a low‐cost alternative to hatchery rearing that is presumed to improve adaptation to local natural conditions. The Shoshone‐Bannock Tribes began supplementing Chinook Salmon Onchorynchus tschwytscha in Panther Creek, Idaho, at the eyed egg stage in 2014. The Chinook Salmon eggs were artificially fertilized and reared to eye‐up in the hatchery and then planted in custom‐made in‐stream incubators (egg boxes) for volitional release and natural rearing. Using data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
(130 reference statements)
2
3
0
Order By: Relevance
“…Our results suggested that egg stocking density increased dispersal of YOY trout from the stocking site, which was consistent with previous studies of brown trout and Atlantic salmon (Einum & Nislow, 2005;Einum et al, 2011;Eisenhauer et al, 2020;Elliott, 1984Elliott, , 1986Elliott, , 1994Milner et al, 2003) and chinook salmon (Oncorynchus tschwytscha; Conley et al, 2020). In contrast, we found that YOY although the negative sign of the correlation aligned with earlier studies of brown trout and Atlantic salmon fry (Einum et al, 2008(Einum et al, , 2011Eisenhauer et al, 2020;Elliott, 1984).…”
Section: Discussionsupporting
confidence: 92%
“…Our results suggested that egg stocking density increased dispersal of YOY trout from the stocking site, which was consistent with previous studies of brown trout and Atlantic salmon (Einum & Nislow, 2005;Einum et al, 2011;Eisenhauer et al, 2020;Elliott, 1984Elliott, , 1986Elliott, , 1994Milner et al, 2003) and chinook salmon (Oncorynchus tschwytscha; Conley et al, 2020). In contrast, we found that YOY although the negative sign of the correlation aligned with earlier studies of brown trout and Atlantic salmon fry (Einum et al, 2008(Einum et al, , 2011Eisenhauer et al, 2020;Elliott, 1984).…”
Section: Discussionsupporting
confidence: 92%
“…In conclusion, our field study demonstrated that RSIs can be used successfully in Michigan streams, building on previous research that has predominately focused on the western USA (Kaeding and Boltz 2004;Arnold et al 2017;Conley et al 2020). We found that removing dead eggs during incubation can effectively reduce the spread of fungus and increase the hatching success in RSIs, especially when RSI flow rate was low.…”
Section: Evaluating Remote Site Incubatorssupporting
confidence: 75%
“…Sedimentation of RSIs was not an issue during our study, suggesting that RSIs may provide an alternative to in-stream incubation techniques at locations where sedimentation is high. Although the method of incubation used by managers is likely to be a function of both watershed characteristics and supplementation goals (Conley et al 2020), comparing the hatching success of RSIs to other stream incubation techniques (e.g., Jordan-Scotty incubators [Purchase et al 2018]) in future studies could provide useful information for managers working to restore native stream fishes.…”
Section: Evaluating Remote Site Incubatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both of the above modeling approaches, failing to account for unmarked, untagged hatchery-origin fish would lead managers to conclude that natural-origin populations were higher than the actual escapement ( Table 3) the South Fork Salmon River (Matala et al 2012), and many of these releases had no distinguishing marks or tags. Additionally, egg box programs, in which hatchery-cultured eggs are placed into in-stream incubators (LSRCP 2019), have been used in tributaries of the Salmon River to reestablish extirpated populations (Conley et al 2020). It is worth noting that unmarked, untagged fish could also be the byproduct of tag loss, imperfect tag detection, fin misclipping rates, or some combination thereof, and that these factors may vary by hatchery.…”
Section: Discussionmentioning
confidence: 99%